Association of cardiothoracic ratio with heart failure hospitalization in patients with atrial fibrillation: the Fushimi AF Registry. (3rd October 2022) - Ikeda, S; Iguchi, M; Ogawa, H; Minami, K; Ishigami, K; Doi, K; Hamatani, Y; Yoshizawa, T; Ide, Y; Fujino, A; Ishii, M; Masunaga, N; et al.
Abstract: Background: Chest radiography is the most common diagnostic imaging test in clinical medicine, and the cardiothoracic ratio (CTR) is a readily available and non-invasive tool with which to assess the volume status and cardiomegaly. However, it remains unknown whether CTR on chest radiography is associated with the incidence of HF hospitalization in AF patients remains unclear. Methods: The Fushimi AF Registry is a community-based prospective survey of AF patients in Fushimi-ku, Kyoto, Japan. The inclusion criterion of the registry is the documentation of AF at 12-lead electrocardiogram or Holter monitoring at any time, and there are no exclusion criteria. We started to enroll patients from March 2011, and follow-up data were available for 4, 489 patients by the end of August 2021. In the present study, 3, 727 patients with available data of CTR were examined. We divided the patients into two groups according to their CTR at baseline; Higher group (CTR ≥50.0%, n=2, 696) and Lower group (CTR <50.0%, n=1, 031), and compared the clinical background and outcomes between the two groups. Results: The proportion of female was grater in Higher group, and the patients in Higher group were older. The patients in Higher group had higher prevalence of HF, hypertension and chronic kidney disease. During the median follow-up of 3, 033 days, in Kaplan-Meier analysis, the incidence rates of HF hospitalization were higher in Higher group (Higher group: 2.5% per person-year vs. Lower group: 1.1%; p<0.01). Multivariate Cox proportional hazards regression analysis revealed that higher CTR (≥50.0%) was an independent determinant of the incidence of HF hospitalization. Furthermore, when we divided the patients into four groups based on the quartile of CTR; Q1 (CTR<49.0%), Q2 (49.0≤CTR<53.8%), Q3 (53.8≤CTR<59.0%), Q4 (59.0%≤CTR), the incidence of HF hospitalization was more frequent in patients with higher CTR, regardless of the presence or absence of prior hospitalization for HF (Figure). Conclusion: In Japanese AF patients, patients with higher CTR had significantly higher incidence of HF hospitalization, regardless of the prevalence of prior hospitalization for HF. Funding Acknowledgement: Type of funding sources: None.